Interaction studies between high-density oil and sand particles in oil flotation technology - Lim, M.W.; Lau, E.V.; Poh, P.E.; Chong, W.T. (Elsevier, 2015)
In the event of a sand contamination, the first course of action would be to ensure that a successful flotation is through the detachment of oil from sand for the ease of flotation. It is widely recognized that the initial oil-sand contact is crucial for oil removal and recovery. Due to its high viscosity and adhesive nature, high density bunker oil could pick up any silica particles (sand) of any size at a short contact time as low as several milliseconds. Nevertheless, the resulting detachment of sand particles from oil would vary under different conditions. Therefore, this study aims at investigating the interactions between oil and sand to further understand the detachment process between oil and sand in a flotation process under various conditions including pH, temperature, sand particle size and wettability. An increase in the water content in the sand sample from 0 wt to 12 wt aids the liberation of oil from contaminated sand from 0.7 to 65, due to the presence of thin film of water which weakens the attachment forces between the oil and sand particles. On the other hand, the coarse sand particles of 1.0 mm easily detach themselves from the oil layer compared to finer sand particles of 0.125 mm which implicate that the attachment forces between oil and said particles increase with the decrease in sand particle size. An increase in the solution pH from pH 6 to pH 14 and temperature from 20 degrees C to 60 degrees C also showed an increase in the sand detachment efficiencies from 25.1 to 60.9, and from 15.2 to 85.1 respectively for 1 mm sand particle size. Further verification experiments including the differential zeta potential results and the DLVO theory supported the results of these former detachment studies, whereby differential zeta potential results showed that increase in pH increased the repulsive forces between particles, while the increase in temperature did not significantly affect the interparticle forces. Hence, the enhanced detachment efficiency due to increase in temperature is mainly attributed to the decrease in oil viscosity which reduces the adhesiveness of bunker oil which also facilitates oil liberation. Finally, the results are in good agreement with the oil flotation efficiencies. (C) 2015 Elsevier B.V. All rights reserved.